Cultivating eHealth evaluation leadership. Issue 4 (July 2019) - Lau, Francis
This article discusses eHealth evaluation leadership in terms of the need, key characteristics, and means to cultivate this leadership. It is well known that health leaders with technical informatics skills and prior eHealth adoption experience are more likely to commit to a long-term eHealth vision, are highly motivated, and can navigate through complex adoption issues. However, much less attention is paid to leadership when it comes to electronic health evaluation. The aim here is to engage the eHealth and broader health leadership communities in a dialogue about eHealth evaluation leadership in terms of its importance, the issues involved, and ways to build capacity in Canada and abroad.